'Daddy-callin' Mamas' and 'Jelly Beans': sex work and ribaldry in the blues archive. Issue 3 (December 2021) - Curtis, Bruce
Abstract: I present a thematic overview of sex work and ribaldry in recorded blues songs for the period c.1920–1942. My ambition is primarily documentary, to take up Paul Oliver's insistence that discussion of the blues must ultimately revolve around its 'libidinous hub' and to concretise Abbott and Seroff's characterisation of blues as 'unabashedly licentious a music form as America has ever produced'. Ribald sex work songs are common in the blues archive, but have not been a focus of sustained study. A grasp of the significance of sex work provides a key to decoding creative wordplay, even as the relation between blues performers and real sex work must remain obscure.